High-Mobility Concrete Mixes for Concrete-Filled Steel Tube Structures of Complex Cross-Section - Sopov, Viktor; Dolgiy, Viktor; Latorets, Kateryna; Zhuravlov, Yurii (International Journal of Engineering and Technology, 2018)
Currently, in the technology of concrete and reinforced concrete, a period of revolutionary leap is observed, caused mainly by the use of high-strength and composite materials, complex high-performance chemical and mineral admixtures, disperse reinforcement, etc. In conditions of increased requirements for economy, lower consumption of metal, cement and forest materials, Interest in the builders causes concrete-filled steel tubes.The main requirements for concrete-filled steel tubes and concrete mixtures for its manufacture are considered. The specific features of the selection of the composition of concrete-filled steel tubes are shown. The technique of selection of compositions and results of researches of properties of concrete mixes and concrete-filled steel tubes is presented.Â Â